EFFECTS OF VARYING CURING AGE AND WATER/CEMENT RATIO ON THE ELASTIC PROPERTIES OF LATERIZED CONCRETE - Ata Olugbenga (Civil Engineering Dimension, 2007)
This paper reports the results of investigations carried out on the effect of varying curing age and water/cement ratio on the modulus of elasticity and modulus of deformability of laterized concrete. The test specimens were made with sieved samples of selected grain size ranges of laterite used as fine aggregates to replace sand in normal concrete. Batching was by weight. Three mix ratios of (1:1Â½:3), (1:2:4) and (1:3:6) were used. Water/cement ratio of 0.5, 0.6, 0.7 and 0.75 were used for each of the mix ratios. The specimens were tested at curing ages of seven to 28 days. The results showed that there was a corresponding increase in both modulus of elasticity and modulus of deformability of laterized concrete due to increase in curing ages. The mix proportion, compressive strength and water/cement ratio were found to have significant effects on both modulus of elasticity and modulus of deformability of laterized concrete.